One to One and Face to Face: A Community Based Higher Education Support Strategy Retaining Indigenous Australian University Students - Sharrock, Peta; Lockyer, Helen (The Australian Journal of Indigenous Education, 2008)
Abstract Literature relating to Indigenous Australian students in higher education highlights the need for improving the retention rates of Indigenous students in Australian universities. A cause for concern has been the increasing numbers of Indigenous Australian people experiencing lower progress and completion rates in comparison to non-Indigenous students. The literature suggests that flexible course delivery is a strategy for improving retention rates and participation. This research extends knowledge relating to the effectiveness of providing courses in flexible delivery mode as a retention strategy in Indigenous higher education. It investigates the “reverse block visit” component of a flexi-mode course delivered by the Centre for Aboriginal Studies at Curtin University of Technology in Perth, Western Australia. Initial findings suggest that this community based support strategy may be impacting positively on risk factors contributing to students withdrawing from their studies. Further research is required to explore the validity of this initial data and how the “reverse block visit” from Centre staff may be working to help students to decide to continue studying.